Overweight Risk and Food Habits in Portuguese Pre-school Children - A.M. Machado-Rodrigues; R.A. Fernandes; Maria-Raquel Silva; A. Gama; I. Mourão; H. Nogueira1; V. Rosado-Marques; C. Padez (Journal of Epidemiology and Global Health, 2018)
The relationship between dietary intake and overweight-risk was assessed in 4349 children aged 3–5 years. Eating and sedentary behaviours were assessed by questionnaire. Logistic regressions were used. Children who consumed daily soft-drinks were 1.52 times more likely to be obese, and 72% more likely to be classified as overweight children.